Comparing face-to-face and computer-mediated collaboration when teaching EFL writing skills. Issue 1 (2nd January 2021) - Jiang, Dayu; Kalyuga, Slava; Sweller, John
Abstract: Face-to-face and computer-mediated collaboration have been used extensively in educational practice. However, research on teaching writing skills for English as a foreign language under collaborative conditions has reported mixed or even negative findings. Cognitive load theory can be used to explain many of these contradictory findings. An experiment ( n  = 60) was conducted to compare the effectiveness of face-to-face and computer-mediated collaborative conditions in fostering learners' acquisition of writing skills. The results indicated that the face-to-face instructional condition benefitted learners' development of writing skills more than the computer-mediated communication condition. Evolutionary educational psychology with its distinction between evolutionary primary and secondary skills was used to explain these results. It was suggested that since we have evolved to collaborate in face-to-face contexts, the associated primary skills could be used to leverage the acquisition of the secondary skills required during foreign language writing.